Short review of theories and problems regarding intellect studies - Paulauskas, Zilvinas (Psichologija, 1995)
The aim of this article is to present a short review of the origin of “intellect” notion and evolution of treatment of this concept. The best-known theories of intellect such as structural theories - two-factorial and multifactorial (both theories of equivalent factors, both hierarchic factors) - and dynamic theories (theories of development of intelligence) or the intellect treatment by theory of information are presented in the first part of this paper. In the second part of the article the problem of measurement of intellect, the development of investigation of intelligence and indicators of intellectual abilities such as mental age, intelligence quotient and profile of intellect's structure is described. The last part of this paper deals with current studies in the physiological correlates of intellect and the most actual questions in creating the culture neutral tests.
Keywords: intelligence; theories of intelligence